700MPa grade high-strength earthquake-resistant steel bar and production method thereof

Through the design of niobium vanadium nitrogen microalloyation and the cooling control process, the composite phase structure and carbon nitride precipitation phase are formed, which solves the existing coordinated matching problems of steel bar strength and plasticity, and realizes the development of 700MPa-level high-strength seismic steel bars.

CN119571206BActive Publication Date: 2025-04-29JIANGSU SHAGANG GROUP CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510139206.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-29
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing reinforcement products have low strength levels, which are difficult to meet the needs of large spans, heavy loads, ultra-high-rises and high-safe buildings. While increasing the strength, it is difficult to coordinate plasticity, seismic resistance and welding performance.

Method used

The microalloy design of niobium-vana nitrogen is adopted. Through the control and cooling control process, the high-temperature heating of the steel bars and slow cooling after rolling is achieved, forming a "ferrite + pearlite + bainite" complex phase structure, and contains carbon nitride precipitation phase, which synergizes the strengthening effect of niobium and vanadium.

Benefits of technology

The strength, plasticity, seismic resistance and weldability of the steel bars have been significantly improved, and the development of high-strength seismic resistance steel bars with a yield strength of more than 700MPa has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application provides a 700MPa grade high-strength earthquake-resistant steel bar and a production method thereof, wherein the steel bar comprises 0.24-0.28% C, 0.50-0.80% Si, 1.20-1.60% Mn, 0.165-0.200% V, 0.025-0.050% Nb, 0.026-0.040% Nb, [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the rest are iron and impurities; in the production method, the temperature of the soaking section is 1255~1300℃; water cooling is not adopted during the rolling process; after rolling is completed, it is cooled to room temperature in the air, the temperature of the upper cooling bed is ≥1125℃, and the cooling rate during natural cooling is <1℃ / s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel smelting, and in particular to a 700MPa grade high-strength earthquake-resistant steel bar and a production method thereof. Background Art

[0002] Building structures are developing towards large spans, heavy loads, super-high-rises and high safety (seismic resistance), which places stringent demands on the strength, plasticity, seismic resistance and weldability of building materials, especially steel bars. The existing steel bar products have low strength levels and yield strengths below 600MPa, which are difficult to meet the use requirements; in order to improve the strength of steel bars, the strength is increased through the strong water penetration process, but it is not conducive to plasticity, seismic resistance and welding performance; obtaining steel bars with ultrafine grains can improve strength and plasticity, but it is not conducive to strength-yield ratio / seismic resistance; high alloying can improve strength, plasticity, and seismic resistance, but it affects welding performance and is costly, and it is impossible to improve the strength, plasticity, seismic resistance and weldability of steel bars at the same time. Summary of the invention

[0003] The purpose of this application is to provide a 700MPa high-strength earthquake-resistant steel bar and a production method thereof, which adopts a niobium vanadium nitrogen micro-alloying design and solves the problem of difficulty in coordinating the strength, plasticity, earthquake resistance and weldability of high-strength earthquake-resistant steel bars above 700MPa in the prior art by controlling the cooling process (high temperature heating + slow cooling after rolling).

[0004] In order to achieve one of the above-mentioned invention purposes, an embodiment of the present application provides a production method of 700MPa grade high-strength earthquake-resistant steel bars, wherein the steel bars contain the following components by weight percentage: C: 0.24-0.28%, Si: 0.50-0.80%, Mn: 1.20-1.60%, V: 0.165-0.200%, Nb: 0.025-0.050%, N: 0.026-0.040%, and satisfy [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the rest are iron and unavoidable impurities; wherein [Nb], [V], [N], and [C] are the weight percentages of the corresponding elements;

[0005] The method for producing steel bars comprises heating, rolling and cooling a steel billet having the chemical composition as described above to obtain steel bars, wherein:

[0006] During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1255~1300℃;

[0007] In the rolling process, the steel billet is placed in the rolling mill and rolled into steel bars, and no water cooling is used during the entire rolling process;

[0008] In the cooling process, after rolling is completed, the steel bars are directly sent to the cooling bed to be naturally cooled to room temperature in the air, wherein the temperature of the cooling bed on the steel bars is ≥1125°C, and the cooling rate during natural cooling is <1°C / s.

[0009] In one embodiment of the present application, before the heating process, the process further includes smelting, LF refining and continuous casting processes which are carried out in sequence, wherein: in the LF refining process, vanadium-nitrogen alloy and ferroniobium alloy are added to the ladle upon arrival, the amount of vanadium-nitrogen alloy added is 2-3 kg / t, the vanadium content in the vanadium-nitrogen alloy is 75-80%, the nitrogen content is 5-10%, and the rest is iron and other impurity elements; the amount of ferroniobium alloy added is 0.6-1.2 kg / t, the niobium content in the ferroniobium alloy is 40-45%, and the rest is iron and other impurity elements.

[0010] In one embodiment of the present application, in the LF refining process, nitrogen blowing begins after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to be 850-1000 L / min, the pressure is controlled to be 0.4-0.8 MPa, and the nitrogen blowing time t satisfies the following formula:

[0011] t=λ×(XAB) / 20, where λ is a coefficient related to the molten steel temperature, ranging from 4 to 6;

[0012] X is the target N content of the steel bar;

[0013] A is the increase in N content after the vanadium-nitrogen alloy is added to the molten steel;

[0014] B is the N content of the molten steel itself, ranging from 30 to 60;

[0015] The units of X, A and B are all ppm, and the unit of t is min.

[0016] In one embodiment of the present application, in the smelting process, the deoxidation alloying is performed by adding alloy and slag in the order of silicon-manganese alloy, ferrosilicon alloy and lime, wherein the amount of silicon-manganese alloy added is 20-30 kg / t, the manganese content in the silicon-manganese alloy is 65-70%, the silicon content is 17-20%, and the rest is iron and other impurity elements; the amount of ferrosilicon alloy added is 9-14 kg / t, the silicon content in the ferrosilicon alloy is 70-75%, and the rest is iron and other impurity elements.

[0017] In one embodiment of the present application, in the smelting process, the steel tapping temperature is controlled at 1595~1635°C, and the argon blowing control valve at the bottom of the ladle is opened before steel tapping, and argon is blown throughout the steel tapping process. The argon pressure is controlled at 0.4~0.5MPa in the first 1 / 3 section before steel tapping, and the argon pressure is controlled at 0.3~0.4MPa in the last 2 / 3 section after steel tapping.

[0018] In one embodiment of the present application, in the continuous casting process, the casting speed is controlled to be 3.0~3.6m / min, and the water flow rate of the crystallizer is 1900~2000L / min.

[0019] An embodiment of the present application also provides a steel bar prepared according to the above-mentioned steel bar production method, wherein the steel bar comprises the following components by weight percentage: C: 0.24~0.28%, Si: 0.50~0.80%, Mn: 1.20~1.60%, V: 0.165~0.200%, Nb: 0.025~0.050%, N: 0.026~0.040%, and satisfies [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the remainder is iron and unavoidable impurities; wherein [Nb], [V], [N], and [C] are the weight percentages of the corresponding elements.

[0020] In one embodiment of the present application, the structure of the steel bar includes pearlite, ferrite and bainite, the volume proportion of pearlite is 50~70%, the average size of pearlite clusters is 10~20μm, the pearlite interlamellar spacing is 200~300nm; the average grain size of ferrite is 4~8μm; the volume proportion of bainite is 5~10%.

[0021] In one embodiment of the present application, the structure of the steel bar includes pearlite, ferrite and bainite, the volume proportion of pearlite is 55~65%, the average size of pearlite clusters is 11~16μm, the pearlite interlamellar spacing is 230~270nm; the average grain size of ferrite is 5~6μm; the volume proportion of bainite is 6~8%.

[0022] In one embodiment of the present application, the steel bar includes a carbonitride precipitate phase, the carbonitride precipitate phase size is ≤50nm, and the volume content is ≥3×10 6 Pieces / mm 3 .

[0023] In one embodiment of the present application, the steel bar includes a carbonitride precipitate phase, the carbonitride precipitate phase size is ≤40nm, and the volume content is ≥5×10 6 Pieces / mm 3 .

[0024] In one embodiment of the present application, the yield strength of the steel bar is ≥720MPa, the tensile strength is ≥910MPa, the elongation after fracture is ≥15%, the total elongation at maximum force is ≥10%, and the strength-yield ratio is >1.26.

[0025] One or more technical solutions provided by this application have at least the following technical effects or advantages:

[0026] The production method of 700MPa grade high-strength earthquake-resistant steel bars provided in this application adopts a medium-low carbon content + vanadium nitrogen microalloying design, and solves the problem of coordinated matching of steel bar strength and plasticity through fine grain strengthening and precipitation strengthening; on this basis, the niobium element is introduced, and the tensile strength of the steel bar is improved through phase transformation strengthening and precipitation strengthening of the niobium element, and the technical problem of insufficient strength-to-yield ratio of high-strength steel bars is solved. Through the associated design of carbon, nitrogen, niobium, and vanadium, combined with the development of rolling technology, the strengthening effect of niobium and vanadium is fully exerted, and the limitation of further improving the strength of high-strength steel bars and the technical problem of insufficient strength-to-yield ratio are overcome; through the development of controlled cooling technology (high temperature heating + slow cooling after rolling), the regulation of the "ferrite + pearlite + bainite" complex phase structure is realized, and the steel bar also contains carbonitride precipitation phase, which significantly improves the strength and toughness of the steel. That is, under the synergistic effect of carbon, nitrogen, niobium, and vanadium, the problem of coordinated matching of steel bar strength, plasticity, earthquake resistance, and weldability is solved, and the development of high-strength earthquake-resistant steel bars with a yield strength of more than 700MPa is realized. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present application provides a method for producing a steel bar, wherein the steel bar comprises the following components by weight percentage: C: 0.24-0.28%, Si: 0.50-0.80%, Mn: 1.20-1.60%, V: 0.165-0.200%, Nb: 0.025-0.050%, N: 0.026-0.040%, and satisfies [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the remainder is iron and unavoidable impurities; wherein [Nb], [V], [N], and [C] are weight percentages of the corresponding elements;

[0029] The method for producing steel bars comprises heating, rolling and cooling a steel billet having the chemical composition as described above to obtain steel bars, wherein:

[0030] During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1255~1300℃;

[0031] In the rolling process, the steel billet is placed in the rolling mill and rolled into steel bars, and no water cooling is used during the entire rolling process;

[0032] In the cooling process, after rolling is completed, the steel bars are directly sent to the cooling bed to be naturally cooled to room temperature in the air, wherein the temperature of the cooling bed on the steel bars is ≥1125°C, and the cooling rate during natural cooling is <1°C / s.

[0033] The vanadium-nitrogen microalloying design is adopted to solve the problem of coordinated matching of steel bar strength and plasticity through fine grain strengthening and precipitation strengthening; on this basis, the niobium element is introduced to improve the tensile strength of the steel bar through phase transformation strengthening and precipitation strengthening of the niobium element, and solve the technical problem of insufficient strength-to-yield ratio of high-strength steel bars. Through the associated design of carbon, nitrogen, niobium and vanadium, combined with the development of rolling technology, the strengthening effect of niobium and vanadium is fully exerted, and the limitation of further improving the strength of high-strength steel bars and the technical problem of insufficient strength-to-yield ratio are overcome; through the development of controlled rolling and controlled cooling technology, the regulation of the "ferrite + pearlite + bainite" complex phase structure is realized, and the steel bar also contains carbonitride precipitation phase, which significantly improves the strength and toughness of the steel. That is, under the synergistic effect of carbon, nitrogen, niobium and vanadium, combined with high-temperature heating and slow cooling after rolling, the problem of coordinated matching of steel bar strength, plasticity, seismic resistance and weldability is solved, and the development of high-strength seismic steel bars with a yield strength of more than 700MPa is realized.

[0034] The effects of each chemical component have the following characteristics:

[0035] Carbon (C): A strengthening element that can significantly improve the strength of steel bars. However, too high a carbon content is detrimental to the plasticity, toughness and welding properties of steel. In order to ensure that the steel has good comprehensive properties, the carbon content is controlled to be 0.24~0.28%.

[0036] Silicon (Si): A strengthening element that can simultaneously improve the yield strength and tensile strength of steel bars through solid solution strengthening. Silicon is also a ferrite-forming element, which is beneficial for regulating the organization and optimizing mechanical properties. However, too high a silicon content is not conducive to welding. Taking all factors into consideration, the silicon content is controlled to be 0.50~0.80%.

[0037] Manganese (Mn): Manganese is a commonly used solid solution strengthening element that can significantly improve the strength and toughness of steel. The manganese content in earthquake-resistant steel bars should be designed to be as high as possible; however, if the manganese content is too high, it will increase the hardenability and easily form MnS inclusions, reducing the plasticity of the steel. Taking all factors into consideration, the manganese content is controlled to be 1.20~1.60%.

[0038] Vanadium (V): Vanadium is a strong carbonitride-forming element. Through the precipitation of carbonitrides, it can significantly improve the strength and toughness of steel. However, the strengthening effect of vanadium is affected by the nitrogen content. When the vanadium content is too high, the effect of further improving the strength is not obvious. Taking all factors into consideration, the vanadium content is controlled to be 0.165~0.200%.

[0039] Niobium (Nb): Niobium improves the strength and toughness of steel through precipitation strengthening and fine grain strengthening; niobium-containing steel can promote the formation of hard phase structure (lowering the ferrite transformation temperature and increasing the transformation temperature of pearlite and bainite) through rolling process control, which is beneficial to adjust the strength-plasticity and seismic resistance (yield ratio) of steel bars; but if the niobium content is too high, the billet is prone to cracks during continuous casting. Taking comprehensive considerations, the niobium content is controlled to 0.025~0.050%.

[0040] Nitrogen (N): a solid solution strengthening and precipitation strengthening element, combined with alloying elements niobium and vanadium to form carbonitrides, which improves strength; but too high a content is detrimental to plasticity; too low a content increases the difficulty of smelting, and the role of strengthening elements cannot be fully exerted. Taking all factors into consideration, the nitrogen content is controlled to be 0.026~0.040%.

[0041] A low carbon equivalent + niobium vanadium nitrogen composite strengthening alloy component system was designed. The low carbon equivalent ensures the welding performance of the steel bar. The vanadium element can significantly improve the strength and plasticity of the steel bar through precipitation, solid solution, and fine grain strengthening, but it is not good for the strength-to-yield ratio and affects the seismic performance. The higher the strength grade of the steel bar, the more difficult it is to meet the seismic performance. In order to reduce this effect, the design of the rolling process is coordinated to promote the formation of hard phase structure (reduce the ferrite transformation temperature, increase the transformation temperature of pearlite and bainite), improve the tensile strength of the steel bar, improve the strength-to-yield ratio index of the steel bar, and improve the seismic performance. When niobium and vanadium are added in combination, the binding ability of niobium with carbon and nitrogen is higher than that of vanadium. In order to ensure the full play of the role of niobium and vanadium, the carbon and nitrogen content must be controlled. At the same time, the solid solution strengthening effect of carbon and nitrogen itself also affects the strength, plasticity, and seismic resistance of the steel bar. Therefore, only the synergistic effect of niobium, vanadium, carbon, and nitrogen can ensure the coordinated matching of the strength, plasticity, seismic resistance, and weldability of the steel bar. Taking all factors into consideration, the synergistic strengthening effect is best when [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, and 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77.

[0042] In one embodiment of the present application, before the heating process, the smelting, LF refining and continuous casting processes are also included in sequence, wherein: in the LF refining process, vanadium-nitrogen alloy and ferroniobium alloy are added to the ladle at the station, the amount of vanadium-nitrogen alloy added is 2-3 kg / t, the vanadium content in the vanadium-nitrogen alloy is 75-80%, the nitrogen content is 5-10%, and the rest is iron and other impurity elements; the amount of ferroniobium alloy added is 0.6-1.2 kg / t, the niobium content in the ferroniobium alloy is 40-45%, and the rest is iron and other impurity elements. The addition of vanadium-nitrogen alloy in the LF refining process can increase a certain amount of nitrogen while meeting the vanadium content, which can reduce the amount of nitrogen required for the nitrogen blowing process below, thereby reducing the nitrogen blowing time and shortening the production process as a whole.

[0043] In one embodiment of the present application, in the LF refining process, nitrogen blowing begins after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to be 850-1000 L / min, the pressure is controlled to be 0.4-0.8 MPa, and the nitrogen blowing time t satisfies the following formula:

[0044] t=λ×(XAB) / 20, where λ is a coefficient related to the molten steel temperature, ranging from 4 to 6;

[0045] X is the target N content of the steel bar;

[0046] A is the increase in N content after the vanadium-nitrogen alloy is added to the molten steel;

[0047] B is the N content of the molten steel itself, ranging from 30 to 60;

[0048] The units of X, A and B are all ppm, and the unit of t is min.

[0049] The nitrogen content of the steel bars in this application is relatively high. Nitrogen is increased by blowing nitrogen into the molten steel to increase the nitrogen content in the molten steel. Compared with the existing nitrogen increase process, the process of nitrogen increase by blowing is simple and economical. At the same time, nitrogen blowing can also play a role of soft stirring, making the alloy elements in the molten steel more uniform. Using a higher flow rate of nitrogen for nitrogen blowing can speed up the nitrogen increase rate and avoid the nitrogen blowing time being too long, which causes the nitrogen element to be unable to dissolve in the molten steel and enter the air with the nitrogen. The nitrogen blowing time is calculated according to the target nitrogen content by the above formula, so that the nitrogen content can be controlled more accurately. When blowing nitrogen, turn off the argon gas. After the nitrogen blowing is completed, turn on the argon gas and stir for ≥5 minutes. The LF refining steelmaking temperature is 1545~1565℃.

[0050] In one embodiment of the present application, in the smelting process, the deoxidation alloying is performed by adding alloy and slag in the order of silicon-manganese alloy, ferrosilicon alloy, and lime, wherein the amount of silicon-manganese alloy added is 20-30 kg / t, the manganese content in the silicon-manganese alloy is 65-70%, the silicon content is 17-20%, and the rest is iron and other impurity elements; the amount of ferrosilicon alloy added is 9-14 kg / t, the silicon content in the ferrosilicon alloy is 70-75%, and the rest is iron and other impurity elements. In the smelting process, the deoxidation alloying is performed by first adding the low-priced silicon-manganese alloy, the silicon in the silicon-manganese alloy is used for deoxidation, and after adding the silicon-manganese alloy, the manganese content reaches the target manganese content of the steel bar, and then the ferrosilicon alloy is added to supplement the insufficient silicon content, thereby reducing the alloy cost.

[0051] In one embodiment of the present application, in the smelting process, the tapping temperature is controlled to be 1595~1635℃, and the argon blowing control valve at the bottom of the ladle is opened before tapping, and argon is blown throughout the tapping process. The argon pressure is controlled to be 0.4~0.5MPa in the first 1 / 3 section before tapping, and the argon pressure is controlled to be 0.3~0.4MPa in the second 2 / 3 section after tapping. The argon pressure is relatively high in the early stage of blowing, providing strong soft stirring, so that the added silicon-manganese alloy and ferrosilicon alloy are better dispersed in the molten steel to make the molten steel homogenized, and the later stage is relatively smooth, which is conducive to tapping.

[0052] In one embodiment of the present application, in the continuous casting process, the casting speed is controlled to be 3.0~3.6m / min, and the water flow rate of the crystallizer is 1900~2000L / min. During continuous casting, a large ladle long water nozzle and sealing pad, an immersion water nozzle, and a tundish covering agent are used for full protection casting, and argon is blown through the long water nozzle. In addition, the crystallizer electromagnetic stirring current is 350A, the frequency is 3~5Hz, and the secondary cooling water volume is automatically distributed according to the parameters (L / m) in Table 1 below:

[0053] Table 1 Parameters corresponding to the secondary cooling water ratio

[0054]

[0055] Among them, m, c, and co are correction coefficients related to the steel grade, which are used to adjust the secondary cooling water ratio. The set value of the secondary cooling water ratio = casting speed × m; c and co are the value ranges of m, where co is the upper limit and c is the lower limit.

[0056] Using a faster casting speed and reducing the cooling rate during continuous casting can avoid cracks on the billet surface caused by niobium.

[0057] The embodiment of the present application also provides a steel bar prepared according to the above-mentioned steel bar production method, wherein the steel bar comprises the following components by weight percentage: C: 0.24~0.28%, Si: 0.50~0.80%, Mn: 1.20~1.60%, V: 0.165~0.200%, Nb: 0.025~0.050%, N: 0.026~0.040%, and satisfies [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the remainder is iron and unavoidable impurities; wherein [Nb], [V], [N], and [C] are the weight percentages of the corresponding elements.

[0058] In one embodiment of the present application, the structure of the steel bar includes pearlite, ferrite and bainite, the volume proportion of pearlite is 50~70%, the average size of pearlite clusters is 10~20μm, the pearlite interlamellar spacing is 200~300nm; the average grain size of ferrite is 4~8μm; the volume proportion of bainite is 5~10%.

[0059] In one embodiment of the present application, the structure of the steel bar includes pearlite, ferrite and bainite, the volume proportion of pearlite is 55~65%, the average size of pearlite clusters is 11~16μm, the pearlite interlamellar spacing is 230~270nm; the average grain size of ferrite is 5~6μm; the volume proportion of bainite is 6~8%.

[0060] In one embodiment of the present application, the steel bar includes a carbonitride precipitate phase, the carbonitride precipitate phase size is ≤50nm, and the volume content is ≥3×10 6 Pieces / mm 3 .

[0061] In one embodiment of the present application, the steel bar includes a carbonitride precipitate phase, the carbonitride precipitate phase size is ≤40nm, and the volume content is ≥5×10 6 Pieces / mm 3 .

[0062] In one embodiment of the present application, the yield strength of the steel bar is ≥720 MPa, the tensile strength is ≥910 MPa, the elongation after fracture is ≥15%, the total elongation at maximum force is ≥10%, and the strength-yield ratio is >1.26.

[0063] The technical solution of the present application is further described below in conjunction with some specific embodiments.

[0064] The present application provides the following steel bars of Examples 1 to 5 and Comparative Examples 1 to 3, which are prepared by converter, LF refining, continuous casting, heating, rolling and cooling processes, wherein Table 2 shows the weight percentages of the chemical components of the steel bars of Examples 1 to 5 and Comparative Examples 1 to 3, Table 3 shows the process parameters of the steelmaking process of Examples 1 to 5 and Comparative Examples 1 to 3, Table 4 shows the process parameters of the LF refining process of Examples 1 to 5 and Comparative Examples 1 to 3, Table 5 shows the process parameters of the continuous casting process of Examples 1 to 5 and Comparative Examples 1 to 3, and Table 6 shows the process parameters of the heating, rolling and cooling processes of Examples 1 to 5 and Comparative Examples 1 to 3.

[0065] The structures and properties of Examples 1 to 5 and Comparative Examples 1 to 3 obtained by referring to the standards GB / T13298 "Methods for the examination of metal microstructures", GB / T28900 "Test methods for steel for reinforced concrete" and GB / T228.1 "Metallic materials tensile test Part 1 Room temperature test methods" are shown in Tables 7 and 8.

[0066] Table 2 Chemical composition of examples and comparative examples (wt%)

[0067]

[0068] Table 3 Production process parameters of examples and comparative examples (steelmaking)

[0069]

[0070] Table 4 Production process parameters of embodiments and comparative examples (LF refining)

[0071]

[0072] Table 5 Production process parameters (continuous casting) of the embodiments and comparative examples

[0073]

[0074] Table 6 Production process parameters (heating, rolling and cooling) of examples and comparative examples

[0075]

[0076] Table 7 Organization of Examples and Comparative Examples

[0077]

[0078] Note: In the structure column of Table 7, F stands for ferrite, P stands for pearlite, and B stands for bainite.

[0079] Table 8 Performance of Examples and Comparative Examples

[0080]

[0081] It can be seen from Tables 2 to 8 that the yield strength of the high-strength earthquake-resistant steel bars provided in the implementation mode of the present application is ≥720 MPa, the tensile strength is ≥910 MPa, the elongation after fracture is ≥15%, the total elongation at maximum force is ≥10%, the strength-to-yield ratio is >1.26, and the comprehensive performance is significantly better than that of comparative examples 1 to 3.

[0082] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0083] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.

Claims

1. A method for producing steel bars, characterized in that: The steel bar contains the following components by weight percentage: C: 0.24-0.28%, Si: 0.50-0.80%, Mn: 1.20-1.60%, V: 0.165-0.200%, Nb: 0.025-0.050%, N: 0.026-0.040%, and satisfies [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the rest are iron and unavoidable impurities; wherein [Nb], [V], [N], [C] are the weight percentages of the corresponding elements; The method for producing steel bars comprises subjecting a steel billet having the chemical composition as described above to heating, rolling and cooling to obtain steel bars, wherein: During the heating process, the temperature of the steel billet in the soaking section of the heating furnace is 1255~1300℃; In the rolling process, the steel billet is placed in the rolling mill and rolled into steel bars, and no water cooling is used during the entire rolling process; In the cooling process, after rolling is completed, the steel bars are directly sent to the cooling bed to be naturally cooled to room temperature in the air, wherein the temperature of the cooling bed on the steel bars is ≥1125°C, and the cooling rate during natural cooling is <1°C / s.

2. The method for producing a steel bar according to claim 1, characterized in that: Before the heating process, the process also includes smelting, LF refining and continuous casting in sequence, wherein: in the LF refining process, vanadium-nitrogen alloy and ferroniobium alloy are added to the ladle upon arrival, the amount of vanadium-nitrogen alloy added is 2-3 kg / t, the vanadium content in the vanadium-nitrogen alloy is 75-80%, the nitrogen content is 5-10%, and the rest is iron and other impurity elements; the amount of ferroniobium alloy added is 0.6-1.2 kg / t, the niobium content in the ferroniobium alloy is 40-45%, and the rest is iron and other impurity elements.

3. The method for producing a steel bar according to claim 2, characterized in that: In the LF refining process, nitrogen blowing starts after the ladle is powered on. During nitrogen blowing, the nitrogen flow rate is controlled to 850~1000L / min, the pressure is controlled to 0.4~0.8MPa, and the nitrogen blowing time t satisfies the following formula: t=λ×(XAB) / 20, where λ is a coefficient related to the molten steel temperature, ranging from 4 to 6; X is the target N content of the steel bar; A is the increase in N content after the vanadium-nitrogen alloy is added to the molten steel; B is the N content of the molten steel itself, ranging from 30 to 60; The units of X, A and B are all ppm, and the unit of t is min.

4. The method for producing a steel bar according to claim 2, characterized in that: In the smelting process, the alloy and slag are added in the order of silicon-manganese alloy, ferrosilicon alloy and lime for deoxidation and alloying. The amount of silicon-manganese alloy added is 20-30 kg / t, the manganese content in the silicon-manganese alloy is 65-70%, the silicon content is 17-20%, and the rest are iron and other impurity elements; the amount of ferrosilicon alloy added is 9-14 kg / t, the silicon content in the ferrosilicon alloy is 70-75%, and the rest are iron and other impurity elements.

5. The method for producing a steel bar according to claim 4, characterized in that: During the smelting process, the steel tapping temperature is controlled at 1595~1635℃, and the argon blowing control valve at the bottom of the ladle is opened before tapping. Argon is blown throughout the entire steel tapping process. The argon pressure is controlled at 0.4~0.5MPa in the first 1 / 3 section before tapping, and at 0.3~0.4MPa in the last 2 / 3 section after tapping.

6. The method for producing a steel bar according to claim 2, characterized in that: During the continuous casting process, the casting speed is controlled at 3.0~3.6m / min and the water flow rate of the crystallizer is 1900~2000L / min.

7. A steel bar prepared according to the method for producing a steel bar as claimed in claim 1, wherein the steel bar comprises the following components by weight percentage: C: 0.24-0.28%, Si: 0.50-0.80%, Mn: 1.20-1.60%, V: 0.165-0.200%, Nb: 0.025-0.050%, N: 0.026-0.040%, and satisfies [Nb]+[V]≤0.23%, [V] / [N]≤6.35, 0.28%≤[C]+[N]≤0.31%, 0.67≤([Nb]+[V]) / ([C]+[N])≤0.77, carbon equivalent Ceq≤0.57%, and the remainder is iron and unavoidable impurities; wherein, [Nb], [V], [N], and [C] are the weight percentages of the corresponding elements.

8. The steel bar according to claim 7, characterized in that The structure of steel bars includes pearlite, ferrite and bainite. The volume proportion of pearlite is 50~70%, the average size of pearlite clusters is 10~20μm, the pearlite interlamellar spacing is 200~300nm; the average grain size of ferrite is 4~8μm; and the volume proportion of bainite is 5~10%.

9. The steel bar according to claim 8, characterized in that The structure of steel bars includes pearlite, ferrite and bainite. The volume proportion of pearlite is 55~65%, the average size of pearlite clusters is 11~16μm, the pearlite interlamellar spacing is 230~270nm; the average grain size of ferrite is 5~6μm; and the volume proportion of bainite is 6~8%.

10. The steel bar according to claim 7, characterized in that The steel bar includes carbonitride precipitation phase, the carbonitride precipitation phase size is ≤50nm, and the volume content is ≥3×10 6 Pieces / mm 3 .

11. The steel bar according to claim 10, characterized in that The steel bar includes carbonitride precipitation phase, the carbonitride precipitation phase size is ≤40nm, and the volume content is ≥5×10 6 Pieces / mm 3 .

12. The steel bar according to claim 7, characterized in that The yield strength of the steel bar is ≥720MPa, the tensile strength is ≥910MPa, the elongation after fracture is ≥15%, the total elongation at maximum force is ≥10%, and the strength-yield ratio is >1.26.

Citation Information

Patent Citations

  • High strength anti-seismic reinforcing steel bar and production method thereof

    CN103255358A

  • Niobium-nitrogen micro-alloying HRB 500 E steel bar and production method thereof

    CN110819891A